ИСАЖОН СУЛТОН РОМАНЛАРИДА ОЛАМ ВА ОДАМ КОНЦЕПЦИЯСИ (Scientific journal of the Fergana State University, 2023)
The article covers the concept of peace and man, reflected in the novels by Isajon Sulton. Considering the ideological and artistic essence of the writer's story in terms of postmodernism, an author's understanding of the goals and tasks of humanity facing him in the context of globalization is revealed.